36 Five years on – failure to apply 2010 nice syncope guidelines in a london tertiary centre. (5th June 2017) - Ahluwalia, Nikhil; Sugihara, Conn; Gall, Nicholas
Abstract : Introduction: NICE have recommended clear pathways for assessment of patients with transient loss of consciousness (TLoC), with the aim of reducing unnecessary investigations, the length of hospital admission and aiming for early specialist assessment and better patient outcomes. Methods: A retrospective analysis of electronic case records for all patients referred by A and E for medical assessment in King's College Hospital in July and August 2015 was performed in August 2016. To capture all potential patients, any referral including the words fall, collapse, seizure, syncope, LoC, cardiac arrest or blackout were screened. Patients who did not have TLoC were excluded based on prespecified criteria. The remaining patient records were evaluated against the 2010 NICE guideline audit tool. Results: 2101 patients were referred over 2 months. 192 (9%) were possible TLoC on the basis of the initial referral. After medical assessment, 147 patients were found not to have TLoC. The most common reasons were absence of LoC (75 pts), epileptic seizure with known epilepsy (24 pts) and drug or alcohol intoxication (17 pts). After screening, there were 45 patients (2%, ) with potential TLoC. No patient with TLoC had the all the NICE-mandated minimum data recorded. Unrecorded data included high risk features that should be the basis for TLoC admissions; family history of premature death (40%), collapse during exertion (20%), new or unexplained dyspnoea (18%). Although 82% had a CXR and 76% received CT head, 84% had no recorded postural BP and 24% had no record of an ECG. Only 16% were referred for inpatient evaluation by a cardiologist. The mean length of stay was 7 days, equivalent to 5 bed-years on an annualised basis. However, 20% were discharged without a diagnosis, and 36% did not have any outpatient follow up. Conclusions: Despite clear guidelines, syncope patients still do not receive appropriate initial evaluation, investigation or diagnosis, even in a large tertiary centre with ready access to specialist assessment. Hospital length of stay is long, yet simple diagnostic tests (such as ECGs and postural BPs) are commonly not performed. Screening of all medical referrals based on simple criteria results in a relatively small number of patients with TLoC. Early specialist involvement in patients with syncope would be practically feasible, and would potentially result in better patient outcomes.